Sustainability and tourism public policies in Brazil: : contradictions and opportunities in the horizon of the 2030 Agenda - Gurgel de Lima, Marcelo Augusto; Irving, Marta de Azevedo; Fragelli, Claudia; Nasri, Yasmin; Faico Ferreira, Graciella (RITUR - Revista Iberoamericana de Turismo, 2025)
Following the Rio 92 Earth Summit tendencies, tourism public policies have been globally influenced by the sustainability discourse. This article, based on bibliographical and documental research, aims to examine how tourism public policies narratives translate the sustainability commitment in the Brazilian case, having the 2030 Agenda as an inspiration horizon. In the context of Brazil, this engagement has been expressed in public policies but still in a peripheral and instrumental way, between advances and setbacks, also as a result of numerous contradictions and governmental discontinuities that have marked the country’s recent history. The challenge for the country, on the horizon of the 2030 Agenda, will be to reconstruct tourism policy narratives based on a long term and an ethical and strategic approach to sustainability, in connection with other priorities of the socio environmental agenda.